Modern Directions of the Content of Understanding the Understanding of Scientific Concepts in the Elementary Grades (Eurasian Scientific Herald, 2023)
In this article, the stages of the formation of concepts in the school are presented in detail, the formation of which is divided into fourteen stages. There is also a scheme of the stages of formation of concepts that is considered the most convenient, and a sequence of its stages is cited.